Knowledge, Awareness, and Practice Regarding Hypothyroidism among Graduate Female Population of a Private University in Dhaka, Bangladesh - Ponni, Afsana Fatema; Khalil, Marjana; Md Aktaruzzaman (PT Inovasi Pratama Internasional, 2024)
Hypothyroidism is chronic disease that occurs due to insufficient release of thyroid hormone. Since there is no permanent cure or treatment for hypothyroidism, controlling the disease or the thyroid hormone level is the only way to deal with this disease, which is not so easy. The symptoms of hypothyroidism may vary widely, especially in different age groups. The objective of this study was to determine the level of knowledge, awareness, attitude & practice among the graduate female population in Dhaka City Among the 200 participants of this study. In this survey, the population was mostly students. So, most of the participants have certain knowledge about the disease. 76% people have proper knowledge about it, that hypothyroidism occurs due to decreased secretion of thyroid hormone, whereas 11.5% people have wrong idea about it & 9.5% people of the population did not know about hypothyroidism. There were also several misapprehensions regarding hypothyroidism, 46.50% of the population thought that Hypothyroidism can be treated using iodized salt, 27% of the population believed Thyroid medications should be stopped during pregnancy, 12% of the population had thought Hypothyroidism is contagious. About 75% population belief that hypothyroidism might cause infertility. Most of the population think that hypothyroidism is more susceptible to women rather than men. Almost 65.50% population thinks like that. About 12.41% participants think that hypothyroidism can be identified by a thyroid stimulating hormone or TSH test, while the other 15.51% believed that hypothyroidism can be diagnosed by a T4 or Thyroxine test. The study found that 64% of family members are not suffering from hypothyroidism, while 36% are unaffected. Additionally, 75% of the population has not been screened for hypothyroidism, and 25% have been screened. Regarding diet, 58% consume iodine-rich fruits, 36% avoid iodine-rich foods, but 64% regularly include iodine-rich foods in their meals.